Improving the sensitivity verification method of the UHF PD detection technique for GIS - Ito, Takashi; Kamei, Mitsuhito; Ueta, Genyo; Okabe, Shigemitsu (IEEE transactions on dielectrics and electrical insulation, 2011)
In the paper, several proposals to improve the sensitivity verification method for the application of UHF partial discharge monitoring systems in GIS, as described in CIGRE Electra No. 183, are presented. Verification results, which depend on the rise time of the test pulse signal, have previously been proposed to compensate for the various rise time pulses with their voltage magnitudes. As a complementary test method to the CIGRE Electra method, a network analyzer measurement is proposed. The influence of the rise time was experimentally investigated using a test GIS setup that had two internal type PD couplers. The scattering parameters of the test GIS were measured, and the computer simulation results corresponded well with the measurement results. The CIGRE method was applied to a 400 kV GIS and the test results of two different rise time conditions were analyzed. An increase of the magnitude due to a longer coaxial cable was demonstrated. The network analyzer method enables compensation of the test pulse specifications, and the scattering parameter data can be used to obtain a GIS trade certificate with the PD coupler. Pulse generators with a rise time shorter than 500 ps are subject to export control regulations when implementing the CIGRE method internationally, which makes the network analyzer advantageous in that it is free from this regulation in terms of using it for UHF measurements.